A hora da existência na temática, na linguagem e na narrativa de Clarice Lispector - Martins, Isa Ferreira (2006)
This work aims at presenting a study on the existential character of Clarice Lispector s thematic, language and narrative. Our motivation was initiated by some discussions and texts about The Hour of the Star occupying an atypical place in Lispector s literary production as a novel that has a social approach, gaining preeminence among the author s other works. Thus, we show that Clarice Lispector, in The Hour of the Star, also raises, fundamentally, existential questions through the individual and subjective bias that is applied to dramatize the conflicts. In such a way, we made comparisons between The Hour of the Star and other Lispector s works so as to show the continuity of the style, of the introspective, reflexive and existential character of Clarice Lispector s literature.